창업지원정책이 기업가정신에 미치는 영향: 중소벤처기업부 팁스(TIPS) 지원사업을 중심으로 - 김미주(Mijoo Kim) (벤처창업연구, 2022)
This study studied the effect of the TIPS support project of the Ministry of SMEs and Startups on the entrepreneurship of TIPS start-ups. The Tips start-up company, which is the subject of the study, was selected for the TIPS support project, participated in all commercialization funds, incubation facilities, and capacity building programs, and was selected as a company that received private investment. One-on-one in-depth interviews were conducted for about eight weeks from January 14, 2022 to March 11, 2022. For this study, the TIPS support project was subdivided into four categories: commercialization funds, incubation facilities, capacity building programs, and private investment attraction, and entrepreneurship factors were classified into four categories: innovation, challenge spirit, leadership, and risk-taking. As a result of the in-depth interview, the influence of the TIPS support project on entrepreneurship factors was in the order of challenge spirit, innovation, risk-taking, and leadership. Specifically, it was found that commercialization funds influenced innovation and risk-taking, incubation facilities had a challenge spirit and risk-taking, competency-building programs had a challenge spirit and leadership, and attracting private investment had an influence on innovation and challenge spirit. The implications of this study are that the TIPS support project, a private investment-led technology start-up support program, was introduced in 2013 and as of the end of March 2022, and a report was prepared focusing on visible performance such as private investment performance and employment rate. However, through this study, by analyzing whether the TIPS support project contributed to the cultivation of entrepreneurship for TIPS start-ups, it was found that it had a positive influence not only on quantitative growth but also on qualitative growth. 본 연구는 중소벤처기업부 팁스(TIPS) 지원사업이 팁스 창업기업의 기업가정신에 미치는 영향에 대해 연구하였다. 연구대상에 해당하는 팁스 창업기업은 팁스(TIPS) 지원사업에 선정되어 사업화자금, 보육시설, 역량강화 프로그램에 모두 참가하였고, 민간투자 유치까지 받은 기업으로 선정하였다. 팁스 창업기업 13개사를 대상으로 2022년 1월 14일부터 2022년 3월 11일까지 약 8주간 1:1 심층 인터뷰를 진행하였다. 본 연구를 위해 팁스(TIPS) 지원사업을 세분화하여 사업화자금, 보육시설, 역량강화 프로그램 그리고 민간투자 유치 총 4가지로 분류하였으며, 기업가정신 요인은 혁신성, 도전정신, 리더십, 위험감수 총 4가지로 구분하였다. 심층 인터뷰 결과, 팁스(TIPS) 지원사업이 기업가 정신 요소에 미치는 영향력은 도전정신, 혁신성, 위험감수, 리더십 순으로 나타났다. 구체적으로 살펴보면 사업화자금은 혁신성과 위험감수, 보육시설은 도전정신과 위험감수, 역량강화 프로그램은 도전정신과 리더십, 민간투자 유치는 혁신성과 도전정신에 영향력을 미치는 것으로 나타났다. 본 연구의 시사점은 민간투자 주도형 기술창업지원 프로그램인 팁스(TIPS) 지원사업이 2013년 도입 후 2022년 3월 말 기준으로 약 10년 차를 맞이하였으며, 그간 민간투자실적, 고용률 등 가시적인 성과 중심으로 보고서가 작성되었다. 또한, 본 연구를 통해 팁스(TIPS) 지원사업이 팁스 창업기업에게 기업가정신 함양에 기여했는지를 분석해봄으로써 양적 성장뿐 아니라 질적 성장에도 긍정적인 영향력을 미치고 있다는 것을 알 수 있었다.